Maternal and Perinatal Outcomes in Uncorrected Tetralogy of Fallot - Khanisyah Erza Gumilar; Christina Meilani Susanto; Erry Gumilar Dachlan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Tetralogy of Fallot (TOF) is the most common congenital heart disease in the population.Correction of TOF during infancy or childhood may increase the quality of patient’s life. Uncorrected TOFmay cause further complications later on. Pregnancy with uncorrected TOF may cause complications onboth maternal and fetal sides.Objective: to analyze maternal and perinatal outcomes in patients with uncorrected TOF during pregnancy.Methods: This is a retrospective study. A total of 8 pregnant women diagnosed with TOF registered inthe Obstetric-Cardiac unit in 3 years (2016-2018). Medical records were reviewed for clinical assessment,echocardiography results, and therapy during hospitalization. Patients were contacted by telephone to providean obstetric history, including details of pregnancy and delivery. Five of 7 patients able to be contacted, andhome visits were done to evaluate their conditions.Results: There were 8 pregnant women with uncorrected TOF. Most cases (87,5%) were first diagnosedduring pregnancy and delivery. Intra-Uterine Growth Restriction (IUGR) and abortion (62.5% and 25%,respectively) were the most obstetric complications. Cardiac complications were cardiogenic shock (12.5%),thromboembolic (12.5%), and various degree of heart failure (62.5%). The number of Small for GestationalAge (SGA) was 66.7%. Incidence of congenital heart disease (CHD) in the fetus was 20%. One death caseand 2 abortions from a total of 8 cases were found.Conclusion: TOF may cause many maternal and fetal complications. The most common maternalcomplications are heart failure, cardiogenic shock and thromboembolic, while perinatal complicationsinclude IUGR, SGA and abortion.